Land use changes and their catchment-scale environmenta limpact in the Polish Western Carpathians during transition from centrally planned to free-market economics - Bucała-Hrabia, Anna. Autor (IGiPZ PAN, 2018)
Land use and land cover changes (LULC) and their impact on potential soil erosion, road density as transfer routes of material and water to channels as well as channel level changes were studied in three catchments (~20 km2 each) in the central part of the Polish Western Carpathians in 1975-2015. It was hypothesised that short-term LULC changes during transition from a centrally planned to a free-market economy are sufficient to modify selected elements of the environment and that these changes can be identified in a measurable way. The analysis of aerial photographs and socio-economic data indicates that during the investigated period, the forest area increased by 20-27%, with a continuous decrease of cultivated land by 89-93% in the three catchments. LULC changes were accompanied by continuous population density growth by 29-50% and a decrease of the population dependent only on agriculture to less than 5%. Analyses confirmed the hypothesis that the environment was significantly modified due to the LULC changes. Abandonment of cultivated land, forest succession and a decrease in used road density, have resulted in lower efficiency of slope wash and sediment transport within the 4th-order catchments. This has led to an interruption of aggradation and initiated channel deepening by approximately 1 cm∙year-1 after the introduction of a free-market economy in 1989.
24 cm
Keywords: LULC; human impact; socio-economic transformation; catchment; Carpathians